2020
DOI: 10.3389/fphys.2020.00126
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of TRPC Channels to Intracellular Ca2 + Dyshomeostasis in Smooth Muscle From mdx Mice

Abstract: Duchenne muscular dystrophy (DMD) is an irreversible muscle disease characterized by a progressive loss of muscle function, decreased ambulation, and ultimately death as a result of cardiac or respiratory failure. DMD is caused by the lack of dystrophin, a protein that is important for membrane stability and signaling in excitable cells. Although vascular smooth muscle cells (VSMCs) dysfunction occurs in many pathological conditions, little is known about vascular smooth muscle function in DMD. We have previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 65 publications
3
34
0
Order By: Relevance
“…This pathway's identity is not fully understood; however, the involvement of TRPCs, which are highly expressed in skeletal muscle cells, has been suggested (Vandebrouck et al, 2002;Millay et al, 2009). A similar aberrant elevation in [Ca 2+ ] i and [Na + ] i have been observed in muscle cells from patients with Duchene's muscular dystrophy and mdx mice (Lopez et al, 1987;Altamirano et al, 2014b;Lopez et al, 2017Lopez et al, , 2020 where an abnormal Ca 2+ influx has also been reported (Tutdibi et al, 1999;Kruger et al, 2008;Millay et al, 2009). Thus, if it were possible to prevent this chronic elevation of [Ca 2+ ] i during aging, it may exert a myo-protective effect and potentially prevent the muscle wasting and dysfunction observed in the aging muscle.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This pathway's identity is not fully understood; however, the involvement of TRPCs, which are highly expressed in skeletal muscle cells, has been suggested (Vandebrouck et al, 2002;Millay et al, 2009). A similar aberrant elevation in [Ca 2+ ] i and [Na + ] i have been observed in muscle cells from patients with Duchene's muscular dystrophy and mdx mice (Lopez et al, 1987;Altamirano et al, 2014b;Lopez et al, 2017Lopez et al, , 2020 where an abnormal Ca 2+ influx has also been reported (Tutdibi et al, 1999;Kruger et al, 2008;Millay et al, 2009). Thus, if it were possible to prevent this chronic elevation of [Ca 2+ ] i during aging, it may exert a myo-protective effect and potentially prevent the muscle wasting and dysfunction observed in the aging muscle.…”
Section: Discussionmentioning
confidence: 91%
“…Among the TRPCs, in skeletal muscle, TRPC3 is the most expressed, followed by TRPC1 and TRPC6 ( Kunert-Keil et al, 2006 ). TRPC channels have been implicated in the pathogenesis of diverse muscle diseases, in particular muscle dystrophies and myasthenia gravis ( Kruger et al, 2008 ; Gailly, 2012 ; Mijares et al, 2014 ; Sauc and Frieden, 2017 ; Lopez et al, 2020 ). Furthermore, overexpression of a dominant-negative form of TRPC6 (dnTRPC6) in this TRPC3 overexpression background reverted its dystrophic phenotype as well as reverting the dystrophic phenotype both in mdx and in Scgd mouse ( Millay et al, 2009 ; Burr et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies show that in dystrophic colonic muscle, increased Ca 2+ influx through Ltype voltage-dependent channels is responsible for the sustained mechanical tone. A recent study showed that the enhanced stretch-induced Ca 2+ i concentration in the vascular smooth muscle cells of mdx mice occurs through the activation of TRPC1, TRPC3, and TRPC6 channels (Lopez et al, 2020). Thus, focusing on the Ca 2+ handling in dystrophic smooth muscle cells may have therapeutic implications.…”
Section: Calcium Handling In Dystrophin-deficient Smooth Musclesmentioning
confidence: 99%
“… 11 13 There is ample evidence that SKF-96365 is widely used to study the function of TRPC channels. 12 17 Previous reports indicate that SKF 96365 could suppress cardiomyocyte hypertrophy, and inhibit spontaneous nociception and pain hypersensitivity induced by melittin via inactivating TRPC channels and Ca 2+ influx. 12 , 18 In cultured NECs, TRPC6, STIM1, Orai1, Ca 2+ MFI levels, and inflammatory mediators were upregulated by lipopolysaccharide (LPS) and 1-oleoyl-2-acetyl-glycerol (OAG, diacylglycerol (DAG) analog, TRPC6 activator), but were inhibited by SKF-96365.…”
Section: Introductionmentioning
confidence: 99%